Apache Spark Deep Learning cookbook : access to 80 enriched recipes that streamline Deep Learning in a distributed environment with Apache Spark /: access to 80 enriched recipes that streamline Deep Learning in a distributed environment with Apache Spark. (2018) - Sherif, Ahmed; Ravindra, Amrith
No abstract available